Risk factors for vertical transmission of hepatitis C virus: a single center experience with 710 HCV-infected mothers. (November 2015) - Garcia-Tejedor, Amparo; Maiques-Montesinos, Vicente; Diago-Almela, Vicente José; Pereda-Perez, Antonio; Alberola-Cuñat, Vicente; López-Hontangas, José Luís; Perales-Puchalt, Alfredo; Perales, Alfredo
Abstract: Objective: The aim of this study was to analyze the risk factors on the perinatal transmission of hepatitis C virus (HCV). Study design: A retrospective cohort study with 711 infants born to 710 HCV-infected mothers was conducted at the Hospital La Fe, in Valencia, Spain, from 1986 to 2011. As potential risk factors for transmission we analyzed: maternal age, mode of acquisition of HCV infection, HIV co-infection, antiretroviral treatment against HIV, CD4 cell count, HIV and HCV viral load, liver enzyme levels during pregnancy, smoking habit, gestational age, intrapartum invasive procedures, length of rupture of membranes, length of labor, mode of delivery, episiotomy, birth weight, newborn gender and type of feeding. Results: Overall perinatal HCV transmission rate was 2.4%. The significant risk factors related with HCV transmission were maternal virus load >615 copies/mL (OR 9.3 [95% CI 1.11–78.72]), intrapartum invasive procedures (OR 10.1 [95% CI 2.6–39.02]) and episiotomy (OR 4.2 [95% CI 1.2–14.16]). HIV co-infection and newborn female were near significance ( p = 0.081 and 0.075, respectively). Conclusions: Invasive procedures as fetal scalp blood sampling or internal electrode and episiotomy increase vertical transmission of HCV, especially in patients with positive HCV RNA virus load at delivery.